Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1155/2022/7853310
|View full text |Cite
|
Sign up to set email alerts
|

Teaching with Technology during COVID-19 Pandemic: An Interview Study with Teachers in Indonesia

Abstract: This paper reports on an interview study with eight secondary school teachers in Indonesia regarding their experiences of teaching with technology during the COVID-19 pandemic. Employing semistructured interview questions and geared under a qualitative research approach, the study probes explicitly into (1) the availability of technology access at home, (2) teachers’ difficulties in teaching online, (3) teachers’ ability to adapt during online teaching, and (4) teachers’ experiences of teaching with technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Considering the new era of teaching, instructors who are not willing to develop their computer skills would fail to handle the class with the new generation of learners and to adapt to the world's changes in education. For instance, during the covid-19 pandemic, instructors with low technology skills had problems managing online classes, and it directly affected their students (Rahayu et al, 2022). Moreover, apart from the ability to manage classes, computer self-efficiency also indicates teachers' competency as digital citizens.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the new era of teaching, instructors who are not willing to develop their computer skills would fail to handle the class with the new generation of learners and to adapt to the world's changes in education. For instance, during the covid-19 pandemic, instructors with low technology skills had problems managing online classes, and it directly affected their students (Rahayu et al, 2022). Moreover, apart from the ability to manage classes, computer self-efficiency also indicates teachers' competency as digital citizens.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Mahdy (2020) revealed that the main challenge that online education faced in veterinary medical science was how to learn practical lessons. Also, in most countries, internet connectivity is problematic and this affected teaching and learning using online means during the COVID-19 pandemic (Rahayu, Rahmadani, Syafitri, Prasetyoningsih, Ubaidillah & Tavakoli, 2022). Khobragade, Soe, Khobragade and Abas (2021) supported this view when they found that the barriers in virtual learning among medical students included communication, internet connectivity, and technical problems.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Rahayu et al (2022) in Indonesia was similar to that of Khobragade, Soe, Khobragade and Abas (2021). Khobragade et al sought to find out the barriers in virtual learning among medical students.…”
Section: Impact Of Covid-19 On Students' Academic Performancementioning
confidence: 99%
“…[8]. As a consequence, developing countries that were mainly focused on traditional face-to-face instructions encountered various challenges (e.g., teachers', students', institutional, infrastructural, technological, and logistical) in this sudden transition [9][10][11][12][13]. However, this study primarily focuses on the challenges faced by teachers of primary and secondary level institutions in Bangladesh during the COVID-19 crisis and discusses the possible solutions.…”
Section: Introductionmentioning
confidence: 99%
“…us, issues occurred when teachers were going to create interactive learning resources, present those materials online, offer feedback, and conduct formative assessments [27,28]. On the other hand, according to studies [13,23,29,30], the toughest difficulties that teachers faced during online instruction were mobilizing students' learning attention, maintaining classroom discipline, organizing classroom discussion, motivating students, and giving online feedback. Another review study [10] claimed that due to a lack of technological skills, digital equipment, expertise, management skills, limited access to digital devices, Internet, and psychological issues, teachers in India's schools, colleges, and universities faced numerous challenges when taking online classes.…”
Section: Introductionmentioning
confidence: 99%